2015
DOI: 10.1021/acs.jpcc.5b04589
|View full text |Cite
|
Sign up to set email alerts
|

Pyroelectrically Driven •OH Generation by Barium Titanate and Palladium Nanoparticles

Abstract: The disinfection of bacteria by thermally excited pyroelectric materials in aqueous environments provides opportunities for the development of new means of sanitization. However, little is known about the formation of reactive oxygen species (ROS) at the surface of the thermally excited pyroelectric materials. To investigate the pyroelectrically driven ROS generation we performed OH radical specific measurements of thermally stimulated barium titanate nanoparticles in contact with palladium nanoparticles. Thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 56 publications
2
53
0
Order By: Relevance
“…To inspect if COH was generated in the piezoelectric-induced process,t erephthalic acid (TA)-photoluminescence (PL) method is employed, as COH could react with TA in equal proportion to produce highly fluorescent 2hydroxyterephthalic acid at 425 nm. [5] Drastic PL peak intensity increase occurs with increasing the ultrasonic time (Supporting Information, Figure S15), suggesting the continuous production of COH. Thep lot of COH concentration vs. ultrasonic irradiation time is illustrated in Figure 4f.The COH concentration generated by BiOI 0.926 V 0.074 O 3 far exceeds that by BiOIO 3 ,a nd the average production rates are 1.2 and 3.9 mmol L À1 h À1 for BiOIO 3 Figure S16), further verifying the piezoelectric induced ROSe volution process.…”
Section: Zuschriftenmentioning
confidence: 99%
See 3 more Smart Citations
“…To inspect if COH was generated in the piezoelectric-induced process,t erephthalic acid (TA)-photoluminescence (PL) method is employed, as COH could react with TA in equal proportion to produce highly fluorescent 2hydroxyterephthalic acid at 425 nm. [5] Drastic PL peak intensity increase occurs with increasing the ultrasonic time (Supporting Information, Figure S15), suggesting the continuous production of COH. Thep lot of COH concentration vs. ultrasonic irradiation time is illustrated in Figure 4f.The COH concentration generated by BiOI 0.926 V 0.074 O 3 far exceeds that by BiOIO 3 ,a nd the average production rates are 1.2 and 3.9 mmol L À1 h À1 for BiOIO 3 Figure S16), further verifying the piezoelectric induced ROSe volution process.…”
Section: Zuschriftenmentioning
confidence: 99%
“…Therefore, the superimposition of microscopic polyhedral distortion contributes to the large macroscopic polarization of BiOI 0.926 V 0.074 O 3 . [5] Drastic PL peak intensity increase occurs with increasing the ultrasonic time (Supporting Information, Figure S15), suggesting the continuous production of COH. Here,u ltrasonic agitation was employed as as table irradiation source to provide stress,and NBT was used as aprobe to quantify the CO 2 À concentration.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 2 more Smart Citations
“…Benke et al were the first to verify hydroxyl radicals generated by thermally excited pyroelectric BaTiO 3 -Pd nanoparticles, [35] uncovering the possible pyrocatalytic mechanism and signifying the potential application of pyroelectric effect in catalysis.Ayear later, Jia et al reported the successful pyrocatalytic degradation of RhB,m ethyl orange (MO), and MB using BiFeO 3 as catalysts. [29] Thep yroelectric effect was also applied in the disinfection of 2',7'-dichlorodihydrogluorescin (DCFH) with LiNbO 3 and LiTaO 3 particles as catalysts.…”
Section: Pyroelectric-material-mediated Catalysismentioning
confidence: 99%